PREMIUM RICE PRICE MODELING USING ARIMA MODEL - Pardomuan Robinson Sihombing; Ade Marsinta Arsani; Mohamad Arif Kurniawan; Triana Mauliasih Aritonang; Sigit Budiantono; Nurhidayati Nurhidayati (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2023)
Rice is a food commodity that has a vital role in meeting the basic food needs of most Indonesian people. Therefore the price of rice significantly impacts the availability, accessibility, and stability of the people's social, economic, and welfare. This study aims to model large prices and conduct nighttime with the ARIMA method. The ARIMA model used based on ACF and PACF criteria is ARIMA (1,1,0). ARIMA modeling (1,1,0) satisfies all assumptions of normality, non-heteroskedastic, non-autocorrelation, and model stability. The model's performance is also good in forecasting with MAPE below 10 percent. Based on forecasting results, premium rice prices continue to increase. Implementing this result requires the government to anticipate rice price increases with comprehensive policies and remain calm so that large prices remain stable